Factor structure of the four motor-free scales of the Developmental Test of Visual Perception, 2nd Edition (DTVP-2) - Brown T; Rodger S; Davis A (American Journal of Occupational Therapy)
INTRODUCTION: Visual-perceptual skills of children are often assessed using the Developmental Test of visual Perceptual Skills-2, 2nd Edition (DTVP-2). PURPOSE: The factor structure of the four motor-free DTVP-2 subscales was examined. METHOD: The scores from a sample of 356 healthy children (171 boys and 185 girls) ages 5 to 11 years were used to complete a principal components factor analysis of the 4 subscales. RESULTS: The position-in-space subscale had items load on six factors. The figure ground subscale had items load on five factors. The visual closure scale and form constancy subscales both had four factors. When the four DTVP-2 subscales were combined to form one overall motor-free visual perceptual scale, the items loaded on 21 factors. CONCLUSION: The DTVP-2 and its four motor-free subscales exhibited multidimensionality instead of the expected unidimensional visual-perceptual constructs.